Babad Danghyang Bang Manik Angkeran: Kajian Struktur Dan Fungsi - Manika Jaya, I Ketut; Suardiana, I Wayan; Sulibra, I Ketut Ngurah (Humanis; Vol 17 No 3 (2016), 2016)
Research the Babad Danghyang Bang Manik Angkeran: study of the structure and function against the backdrop of an interesting story from the Babad Danghyang Bang Manik Angkeran and contains lineage of the clan. Research Babad Danghyang Bang Manik Angkeran aims to provide knowledge and insight to traditional Balinese society, that Babad the importance of literature in life, which can provide a living learning of the meaning contained in it. The theory used is the structural theory and the theory of functions. Structural theory used is the structural theory by Jonathan Culler and Darusuprapta. The theory used function is the function theory developed by S.O Robson and Teeuw. In this study, used several methods to simplify the research process. The methods used are: (1) phase of the provision of data using the methods of literary study and consider methods. While the technique used is the technique of translation, (2) the stage of data analysis using qualitative methods, and techniques used are descriptive, and 3) the stage of presentation of the results of data analysis using formal and informal methods. While the technique used is the technique of deductive and inductive techniques. The results of this study are unfolding structures that build Babad Danghyang Bang Manik Angkeran, content, and functionality contained therein. The structure of the building Babad Danghyang Bang Manik Angkeran include characters, plot, and theme. Which shows the whole sequence and intact furthermore, elements Babad Danghyang Bang Manik Angkeran, namely Mythology (angel), Legend (the origin of the Strait of Bali), hagiography (miracle), Symbolic (symbols), and Suggestion (divination). Functionality in the Babad Danghyang Bang Manik Angkeran among which historical function, the function of religious and social functions.